2019
DOI: 10.3354/meps12885
|View full text |Cite
|
Sign up to set email alerts
|

Piscivory in age-0 summer flounder Paralichthys dentatus with a focus on predator-induced mortality of post-settlement winter flounder Pseudopleuronectes americanus

Abstract: for 0.7% of the daily mortality of post-settlement winter flounder (range = 0.0−2.9%), and consumed 3.0% of the total winter flounder year-class annually (range = 0.0−12.8%). Therefore, relative to other predatory fishes and decapod crustaceans, age-0 summer flounder likely have a nominal effect on winter flounder populations in tidal river nurseries. Summer flounder predation may be substantial, however, when multiple age-classes are considered and elevated age-0 summer flounder densities elicit a strong effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 54 publications
1
5
0
Order By: Relevance
“…The projections of the No Fishing and Business As Usual scenarios indicate that under present conditions absent harvest or present conditions with projected warming of summer water temperatures due to climate change, high rates of juvenile mortality make recovery of Narragansett Bay winter flounder very unlikely. This is largely in agreement with past work indicating that predation (Manderson et al, 1999, 2006; Sagarese et al, 2011; Taylor et al, 2019; Taylor & Collie, 2003), low dissolved oxygen (Dolan et al, 2021; Pereira et al, 1999), and warming temperatures (Dolan et al, 2021; Gallagher et al, 2015; Pereira et al, 1999; Taylor & Collie, 2003) can limit winter flounder productivity. The low probability of recovery observed in the No Fishing scenario supported the hypothesis that the current depleted state of this subpopulation is not primarily the result of harvest pressure.…”
Section: Discussionsupporting
confidence: 93%
“…The projections of the No Fishing and Business As Usual scenarios indicate that under present conditions absent harvest or present conditions with projected warming of summer water temperatures due to climate change, high rates of juvenile mortality make recovery of Narragansett Bay winter flounder very unlikely. This is largely in agreement with past work indicating that predation (Manderson et al, 1999, 2006; Sagarese et al, 2011; Taylor et al, 2019; Taylor & Collie, 2003), low dissolved oxygen (Dolan et al, 2021; Pereira et al, 1999), and warming temperatures (Dolan et al, 2021; Gallagher et al, 2015; Pereira et al, 1999; Taylor & Collie, 2003) can limit winter flounder productivity. The low probability of recovery observed in the No Fishing scenario supported the hypothesis that the current depleted state of this subpopulation is not primarily the result of harvest pressure.…”
Section: Discussionsupporting
confidence: 93%
“…Winter flounder is a known prey item for summer flounder in estuarine systems (Poole, 1964;Manderson et al, 2000), but only our study and a recently published study in New England (Taylor et al, 2019) have reported winter flounder as the most important (% by weight and % frequency, respectively) prey item for summer flounder. Previous research in Great South Bay (New York) reported sand shrimp as the main prey item for summer flounder, and winter flounder as the secondary prey item (Poole, 1964).…”
Section: Importance Of Winter Flounder As Preymentioning
confidence: 53%
“…Comparisons between bays were hindered by low statistical power, likely due to uncertainty associated with estimating mortality utilizing survey-based abundance approaches. However, consistent mortality estimates across bays could also be a symptom of climate-driven synchronization of nursery production (Manderson 2008) and/or trophic interactions with other species that are more directly impacted by climate (Liebhold et al 2004;Able et al 2014;Taylor et al 2019). To the latter point, predation mortality on age-0 Winter Flounder in Long Island bays can be up to six times greater than other causes of natural mortality (Dolan 2020).…”
Section: Discussionmentioning
confidence: 99%
“…To the latter point, predation mortality on age-0 Winter Flounder in Long Island bays can be up to six times greater than other causes of natural mortality (Dolan 2020). Summer Flounder Paralichthys dentatus may consume up to ~60% of the age-0 Winter Flounder within the immediate area during peak settlement (Taylor et al 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation